2010
DOI: 10.1080/13623699.2010.535279
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, crime and access to basic needs before and after the Haiti earthquake: a random survey of Port-au-Prince households

Abstract: On 12 January 2010 an earthquake measuring 7.0 on the Richter Scale struck Haiti, causing unprecedented death, injury and destruction for an event of this magnitude. Our aim was to generate a rapid assessment of the primary consequences for the population of the metropolitan area of Port-au-Prince, the national capital. During the summer of 2009 we conducted a survey of 1,800 households in metropolitan Port-au-Prince. Six weeks after the earthquake, we attempted to trace these households in order to re-intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 3 publications
2
111
1
1
Order By: Relevance
“…Billions of dollars were spent by international funding agencies that promoted NGOs as substitutes for the state which weakened the government [13,43]. Nevertheless, farmers reported receiving no support, leading to increased crime, mortality, and hunger [44]. There were limited efforts by FAO to support the Government of Haiti's Programme of Action to rebuild the agricultural sector, improve food security, and create employment and livelihood opportunities for the rural population and internally displaced people [42].…”
Section: Haitian Earthquakementioning
confidence: 99%
“…Billions of dollars were spent by international funding agencies that promoted NGOs as substitutes for the state which weakened the government [13,43]. Nevertheless, farmers reported receiving no support, leading to increased crime, mortality, and hunger [44]. There were limited efforts by FAO to support the Government of Haiti's Programme of Action to rebuild the agricultural sector, improve food security, and create employment and livelihood opportunities for the rural population and internally displaced people [42].…”
Section: Haitian Earthquakementioning
confidence: 99%
“…Studies from Haiti (Kolbe et al 2010) and Taiwan (Chou et al 2004) found children to be at higher risk of death, and both reported similar odds ratios of 5.8 (95 % CI 4, 8.3) and 5.5 (95 % CI 4.4, 6.8), respectively.…”
Section: Individual and Household Characteristics And Earthquake-indumentioning
confidence: 73%
“…These criteria used to screen all abstracts included. Thirteen studies met these criteria and were included in this section (Shoaf et al 1998;Mahue-Giangreco et al 2001;(Liang et al 2001;Peek-Asa et al 2003;Chou et al 2004;Doocy et al 2009Doocy et al , 2013Ellidokuz et al 2005;Dong et al 2012;Kolbe et al 2010;Osaki and Minowa 2001;Roces et al 1992;Armenian et al 1992). The steps of the literature review are described in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Women, children 96 and the elderly were identified as being more likely to have died at the time of the earthquake 97 . Women 27, 38, 39, 47, 59, 67, 98-102 , children 38 , elderly 38 and those with disabilities 103 were also reported as being disproportionately affected both with regard to earthquake-related injuries as well as other more routine health presentations.…”
Section: Inequality Of Impactmentioning
confidence: 99%